2021
DOI: 10.3389/fphar.2021.695486
|View full text |Cite
|
Sign up to set email alerts
|

Fructose Metabolism and Cardiac Metabolic Stress

Abstract: Cardiovascular disease is one of the leading causes of mortality in diabetes. High fructose consumption has been linked with the development of diabetes and cardiovascular disease. Serum and cardiac tissue fructose levels are elevated in diabetic patients, and cardiac production of fructose via the intracellular polyol pathway is upregulated. The question of whether direct myocardial fructose exposure and upregulated fructose metabolism have potential to induce cardiac fructose toxicity in metabolic stress set… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 100 publications
1
9
0
Order By: Relevance
“…This observed trend is largely driven by modifiable lifestyle factors, including insufficient physical activity and an unhealthy diet [ 3 ]. An essential dietary determinant of T2DM is the increased consumption of refined sugars, in the form of glucose, fructose and sucrose, used extensively in the food industry [ 4 , 5 ]. Cohort studies have demonstrated an association between sugar-sweetened beverages and foods and the incidence of T2DM and diabetes-related comorbidities, including cardiovascular diseases (CVD) [ 6 , 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…This observed trend is largely driven by modifiable lifestyle factors, including insufficient physical activity and an unhealthy diet [ 3 ]. An essential dietary determinant of T2DM is the increased consumption of refined sugars, in the form of glucose, fructose and sucrose, used extensively in the food industry [ 4 , 5 ]. Cohort studies have demonstrated an association between sugar-sweetened beverages and foods and the incidence of T2DM and diabetes-related comorbidities, including cardiovascular diseases (CVD) [ 6 , 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, despite comparable caloric intake and weight gain, the consumption of glucose-sweetened beverages over a 10-week period does not increase visceral adiposity [ 76 ]. In addition, fructose promotes inflammation and lipid accumulation in cardiac myocytes and enhances myocardial and vascular superoxide generation [ 77 , 78 ]. Together, these mechanisms conspire to promote hypertension and adverse cardiovascular effects.…”
Section: Discussionmentioning
confidence: 99%
“…Dietary intake is the main extracellular source of fructose, which enters the cardiomyocytes via the systemic circulation. The intracellular source is the polyol pathway, wherein glucose is reduced to sorbitol by aldose reductase and sorbitol is then oxidized to fructose by sorbitol dehydrogenase (SDH) ( 14 ).…”
Section: Fructose and Lactatementioning
confidence: 99%
“…Fructose exposure is associated with metabolic disorders, lipid accumulation, inflammation, and apoptosis ( 108 , 109 ). Increased cellular fructose metabolism promotes the formation of O-Glcnacylation and AGEs, which are crucial for fructose-mediated cardiomyocyte signaling and dysfunction ( 13 , 14 ).…”
Section: Fructose and Lactatementioning
confidence: 99%
See 1 more Smart Citation